2013
DOI: 10.1186/1471-2431-13-149
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with physical growth of children during the first two years of life in rural and urban areas of Vietnam

Abstract: BackgroundDifferences between urban and rural settings can be seen as a very important example of gaps between groups in a population. The aim of this paper is to compare an urban and a rural area regarding child growth during the first two years of life as related to mother’s use of antenatal care (ANC), breastfeeding and reported symptoms of illness.MethodsThe studies were conducted in two Health and Demographic Surveillance Sites, one rural and one urban in Hanoi, Vietnam.ResultsWe found that children in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 41 publications
(54 reference statements)
1
24
0
6
Order By: Relevance
“…Low level of household wealth is also a background characteristic contributing to the prevalence of undernourished children (13,(15)(16)(17)(18) . While low household income has a negative effect on children's nutritional status, education acts as a protective factor following the pattern that children whose mothers have higher or high education are more likely to be well-nourished Some studies have confirmed that mother's education is one of the main determinants of undernutrition (12)(13)(14) . Also, it has been shown that children whose mother was more educated were more likely to consume the optimal amounts of protein, Ca and vitamins necessary for their proper physical and psychological growth (19) .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Low level of household wealth is also a background characteristic contributing to the prevalence of undernourished children (13,(15)(16)(17)(18) . While low household income has a negative effect on children's nutritional status, education acts as a protective factor following the pattern that children whose mothers have higher or high education are more likely to be well-nourished Some studies have confirmed that mother's education is one of the main determinants of undernutrition (12)(13)(14) . Also, it has been shown that children whose mother was more educated were more likely to consume the optimal amounts of protein, Ca and vitamins necessary for their proper physical and psychological growth (19) .…”
mentioning
confidence: 99%
“…To date, different studies have shown that various indicators of socio-economic status are associated with children's nutritional status, such as educational level of parents, parental income and family assets (10)(11)(12)(13)(14) . Poverty, which is very typical for low-and middle-income countries, is one of the main risk factors for child undernutrition.…”
mentioning
confidence: 99%
“…Embora estudo realizado no Vietnã tenha mostrado que o risco de diarreia infantil seja maior na zona rural quando comparada à zona urbana (10) , percebeu-se durante a execução da presente pesquisa que apesar da maioria das famílias residirem na zona urbana, o número de crianças que apresentou episódios diarreicos prévios foi superior às que não apresentaram.…”
Section: Discussionunclassified
“…Bayi dengan BBLR berisiko mengalami gangguan pertumbuhan, seperti pada penelitian Nguyen et al, (2013) menyebutkan bahwa bayi dengan BBLR sulit mencapai berat badan maupun tinggi badan yang optimal sampai usia 24 bulan. BBLR ini merupakan faktor intermediet pertumbuhan anak yang merupakan indikator status gizi anak, sedangkan yang menjadi underlying factor adalah pendidikan ibu, pekerjaan ibu, dan ekonomi keluarga (Nguyen et al, 2013).…”
Section: Pembahasan 1 Pengaruh Status Gizi Anak Terhadap Kejadian Pnunclassified
“…BBLR ini merupakan faktor intermediet pertumbuhan anak yang merupakan indikator status gizi anak, sedangkan yang menjadi underlying factor adalah pendidikan ibu, pekerjaan ibu, dan ekonomi keluarga (Nguyen et al, 2013). Hal ini mendukung bahwa BBLR berkaitan dengan status gizi anak yang dapat menjadi faktor risiko secara tidak langsung kejadian pneumonia balita.…”
Section: Pembahasan 1 Pengaruh Status Gizi Anak Terhadap Kejadian Pnunclassified